Relationship Between Religion and Secondary School Students’ Performance in Chemistry in Samburu County, Kenya - Ekwam, Lomonyang; Keraro, Fred N.; Ng’eno, Joel K. (American Journal of Education and Practice, 2025)
Purpose: The purpose of this study was to determine the relationship between Religion and secondary school students’ performance in chemistry. In addition to the main purpose, the study sought to investigate the relationship between religion and secondary school students’ performance in chemistry in Samburu County. Materials and Methods: Descriptive Correlational survey research design was used. The target population was all the secondary school chemistry students in Samburu County. The accessible population was all the Form Three chemistry students in the County in the year 2024. Cluster sampling was used to select nine secondary schools as sampling units. This included both public and private schools. Stratified and simple random sampling was used to select a sample of 282 students. Two instruments were used for data collection namely: Students’ Chemistry Performance Test (SCPT) and Students’ Religion Questionnaire (SRQ). The instruments for data collection were validated by five experts in educational research. The reliability coefficient of SCPT and SRQ was estimated using Guttman’s Lambda (λ6) formula. This yielded a reliability coefficient of 0.78 and 0.81 respectively. The data collected was analyzed using both descriptive and inferential statistics. Simple Linear Regression was used to establish the relationships between the different variables in the study. All statistical tests of significance were conducted at a coefficient level of alpha (α) equal to 0.05 with the help of Statistical Package for Social Sciences (SPSS) version 23.0 for windows. Findings: The findings indicate that there was a statistically significant relationship between Religion and students’ performance in chemistry. The findings of this study would also benefit chemistry teachers, curriculum developers, teacher educators, spiritual leaders and policy makers in addressing necessary interventions to facilitate meaningful learning of chemistry and thus improve students’ performance in chemistry in secondary schools Countrywide. Unique Contribution to Theory, Practice and Policy: It is recommended that the Ministry of Education should initiate in-service courses for all science teachers to equip themselves with relevant skills to enhance their effectiveness in teaching of chemistry and science subjects in general.